The Effect Of The Old Level Of Boating On The Success Of Making Sweet Poultry And Kepok Banana - May Wulan Sari; Azis Abdul Malik; Anike Riana; Irvan Ardiansyah Putra; Seri Dewi Ami; Nurlia Latipah (ISEJ : Indonesian Science Education Journal, 2020)
This study aims to determine the effect of the length of boiling time on success in making purple sweet potato tapai and banana kepok. The method used in this research is the experimental method and documentation media. By using observations of purple sweet potato stew and banana kepok. The content that is in purple sweet potato is very much, including as a source of carbohydrates and sources of enough calories (such as vitamins, minerals, protein, fat, and fiber). While kapok bananas contain high carbohydrates and fiber. By means of fermentation, the anaerobic carbohydrate and amino acid breakdown process that is without the need for oxygen. The process of making tapai from purple sweet potato and banana is done by referring to the standard of making tapai in general, only in this study using 2 samples with each different level of maturity. From the results and discussion it can be concluded that the length of boiling time and the level of maturity in making purple sweet potato tapai and banana kepok affect the texture and taste.